Modern Crisis: The Riddle of Varys (London Journal of Research In Humanities and Social Sciences, 2025)
The article is preparatory in nature to consider one of the causes of the current crisis and possible ways out of it. The article considers two rights: the right to preferential distribution and the right to deferred exchange, which together form the basis of consumption in society. Three types of the right to preferential distribution are analyzed, which correspond to three possible types of capital, depending on which of these rights is given the right to violence. It is shown that these three distributive rights are in a state of pressure on each other and form a triad with negative feedback, which ensures the stability of the system and forms the basis of society in the form of a triad: ideology-politics-economics. In conclusion, the riddle of Varys is considered in relation to the topic under consideration.
Keywords: Phenomenology; ASD; late modernity; complex phenomenon; psychotherapeutic discourse; medical discourse; psychotherapeutic discourse integrated into fiction; conceptual metaphor in therapy; agent and client of psychotherapeutic discourse; language representation of feelings and emotions.; existential psychoanalysis; Phenomenological clinic; Environmental devastation; Patriarchal Categories; Ecological Problem; Vandana Shiva.; distributive law; the right to deferred exchange; capital; the triad; the riddle of Varys